PENDIDIKAN MUSIK SEBAGAI SARANA PENGEMBANGAN KREATIVITAS REMAJA GEREJA MASEHI INJILI DI MINAHASA - Stefanny Mersiany Pandaleke; Fian Panekenan (Institut Agama Kristen Negeri Manado, 2020)
Abstract The teenagers of Evangelical Christian Church in Minahasa (GMIM) are the next church’s generation who are transitioning from sunday school group to youth. In their activities, music education exists as a medium of appreciation and development of creativity. This paper discusses about the process of music education in GMIM which acts as a education creativity for teenagers. The purpose of this research is to understand and explain how music education is realized as a medium of developing creativity for GMIM teenagers. This research uses qualitative method, with data collected by observation, interviews and document studies. The data analysis uses appreciation and creation concept in art education, by following the interactive model analysis. The results showed that GMIM teenagers were directly involved in the appreciation process through the their activities in congregation, regional and synod level, which were dominated by musical activities. The process of appreciation is implemented into five phase, that starting from introduction to assessment. Stand on the appreciation activites, GMIM teenagers did the development of creativity, through the preparation, conceptualizing ideas and pouring creative ideas.